Cytological, histological, and molecular characteristics of pure invasive micropapillary carcinoma of pancreas: A case report. Issue 24 (12th June 2020) - Lee, Sun-Jae; Bae, Han-Ik; Yoon, Ghilsuk; Cho, Chang Min; Kwon, Hyung Jun; Park, Jongmin; Cho, Seung Hyun; Seo, An Na
Abstract: Introduction: Pure invasive micropapillary carcinoma (IMPC) is a rare histologic subtype of pancreatic cancer which has a high propensity for lymph node metastasis and poor prognosis. Patient concerns: An 81-year-old woman was admitted to our institution with a 3-month history of back pain. Computed tomography of the abdomen and pelvis confirmed the presence of a low-density mass in the tail of the pancreas. Diagnosis: Endoscopic ultrasound-guided fine needle aspiration cytology (FNAC) from the pancreatic mass showed small tumor cell clusters with three-dimensional aggregates and morula-like structures. The tumor was diagnosed as adenocarcinoma with micropapillary features. Interventions: The patient underwent radical antegrade modular pancreatosplenectomy and regional lymph node dissection. Histological examination showed small clusters of tumor cells that were closely adhered to one another. The cells were located in empty stromal spaces mimicking lymphovascular channels. All tumor cells showed reverse polarity, resulting in an "inside-out" pattern. An extensive search was performed, and no typical ductal adenocarcinoma component was found. The tumor measured 1.5 × 1.3 cm and invaded into the peripancreatic fat tissue without adjacent organ invasion. One of the 12 regional lymph nodes showed metastasis. Ion Torrent next-generation sequencing identified missense mutations in KRAS, TP53, and SMAD4 using the Oncomine Comprehensive Panel version 1. Outcomes: Twelve months following surgical resection the patient remained healthy with no evidence of recurrence at clinical follow-up. Lessons: This report highlights the diagnostic features and molecular characteristics of pure pancreatic IMPC and the challenges with diagnosis by FNAC. A centralized and collaborative accumulation of additional cases of pure IMPC could further elucidate its pathogenesis.